2
$\begingroup$

I'm trying to prove that $$\mathcal{L}\{t^2e^{at}\} = \frac{2}{(s-a)^3}.$$

I've gotten to the last integration by parts where

$$ \lim_{n\to\infty}\int_0^n\frac{1}{(a-s)^22e^{(a-s)t}}dt = \left. \lim_{n\to\infty}\frac{2}{(a-s)^3}e^{(a-s)t} \right|_0^n. $$

Now what do I do? I can't find a way to make that last term converge?

$\endgroup$
4
  • $\begingroup$ It is necessary to assume that $s > a$ here. $\endgroup$
    – user61527
    Nov 21, 2013 at 1:51
  • $\begingroup$ That doesn't really help @T.Bongers; the sign we care about doesn't get switched anyway $\endgroup$
    – Don Larynx
    Nov 21, 2013 at 1:53
  • 1
    $\begingroup$ If $s > a$, then $e^{(a - s)t} \to 0$ for $t$ positive. Then you'll get $$0 - \frac{2}{(a - s)^3} e^0$$ as desired. $\endgroup$
    – user61527
    Nov 21, 2013 at 1:56
  • $\begingroup$ I don't see how; the thing just changes to $$\lim_{n\to\infty}\frac{2}{(s-a)^3}e^{(s-a)t}|_0^n$$...@T.Bongers $\endgroup$
    – Don Larynx
    Nov 21, 2013 at 1:59

1 Answer 1

2
$\begingroup$

Evaluating the integral for a fixed $n$ gives

$$\frac{2}{(a - s)^3} e^{(a - s)n} - \frac{2}{(a - s)^3} e^0$$

Assume that $s > a$ and let $n$ go to infinity. Then since $(a - s) n \to -\infty$, the first term disappears and the limit is

$$-\frac{2}{(a - s)^3} e^0 = -\frac{2}{(-1)^3 (s - a)^3} = \frac{2}{(s - a)^3}$$

$\endgroup$
7
  • $\begingroup$ I DON'T SEE HOW $\lim_{n\to\infty}(s-a)n \to -\infty$????? @T.Bongers $\endgroup$
    – Don Larynx
    Nov 21, 2013 at 2:06
  • $\begingroup$ @DonLarynx If $s - a$ is positive and you multiply it by a huge $n$, then $(s - a)n$ is still a huge number. With a slight abuse of notation, $$\lim_{n \to \infty} (s - a)n = (s - a) \lim_{n \to \infty} n = (s - a) \infty = \infty$$ $\endgroup$
    – user61527
    Nov 21, 2013 at 2:07
  • $\begingroup$ That's positive infinity, not negative infinity. Thus it does NOT converge. That is why I am so distraught. $\endgroup$
    – Don Larynx
    Nov 21, 2013 at 2:09
  • 2
    $\begingroup$ @DonLarynx If $(s - a) n \to \infty$, then $(a - s) n \to -\infty$. $\endgroup$
    – user61527
    Nov 21, 2013 at 2:10
  • $\begingroup$ Then my main question is, why does the latter hold? I don't know why (a - s) has to be positive. $\endgroup$
    – Don Larynx
    Nov 21, 2013 at 2:11

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.